Development of integrated computer-assisted learning model for curriculum support in post-primary schools in Rivers State, Nigeria - Wonu, Chukwumezie Theophilus; Amannah, Constance Izuchukwu (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2024)
A critical issue emerged concerning the lack of an effective and efficient computer-assisted learning model to support the curriculum in post-primary schools in Rivers State. Addressing this challenge, this study employed a combination of waterfall and design science research methods to develop an integrated computer-assisted learning model tailored to the educational settings in Rivers State. The approach involved a comprehensive literature review, a needs assessment survey, and the subsequent design and implementation of the learning model. The designed integrated computer-assisted learning model comprised six essential function modules: curriculum, topic, learning resource, assessment, user, and classroom. The model accommodates various learning activities, including individualized, collaborative, and blended learning. The evaluation of the learning model demonstrates its effectiveness in enhancing student engagement, motivation, and learning outcomes. Notably, the study provides valuable insights into the development and evaluation of such a model in post-primary schools in Rivers State, contributing to the growing body of knowledge on computer-assisted learning. The integrated model proved to promote student-centred learning, foster collaboration, and offer immediate feedback, positively impacting both teachers and students by reducing teacher workload and enhancing student motivation and performance. The study recommends scaling up the implementation of the model in more schools, integrating it with existing curriculum and pedagogy, regularly assessing and reevaluating the curriculum to identify evolving educational needs, and incorporating feedback from educators, students, and stakeholders. These recommendations aim to contribute to the ongoing efforts to improve the quality of education in Nigeria.